Functional Ca2+ Channel Produced by Purified Platelet Membrane Glycoprotein IIb-IIIa Complex Incorporated into Planar Phospholipid Bilayer - Fujimoto, Tetsuro; Fujimura, Kingo; Kuramoto, Atsushi (Thrombosis and Haemostasis, 1991)
The ability of the platelet membrane glycoprotein (GP) IIb-IIIa complex to function as a Ca2+ channel was investigated by electrophysiological methods. The GPIIb-IIIa complex was purified with an electrically silent detergent, CHAPS, and reconstituted into liposomes. After incorporation of these liposomes to a planar phospholipid bilayer, Ba2+-permeable channel currents were detected. Since neither residual detergent nor dissociated GPIIb and IIIa produced any currents, the observed channel currents were attributed to the GPIIb-IIIa complex. These channel currents showed similar electrical properties with the Ca2+ channel previously described in platelet plasma membrane; a single channel conductance of approximately 10 pS in 53 mM Ba2+ solution and voltage-independency. It was concluded that the purified GPIIb-IIIa complex can act as a divalent cation-permeable channel in the artificial phospholipid bilayer.